Synergistic therapy by acyclovir and A1110U for mice orofacially infected with herpes simplex viruses. - Ellis, M N (1989)
Clinical effects of the administration of a combination of acyclovir (ACV) and compound A1110U (a 2-acetylpyridine thiocarbonothiohydrazone inactivator of herpes simplex virus [HSV] ribonucleotide reductase) on the development of herpetic skin lesions were studied in athymic and hairless mice infected intracutaneously with different HSV type 1 (HSV-1) strains. ACV was administered topically (5%) or orally (5 mg/ml), while A1110U was applied topically (3%). In all but one experiment, the effect of combination therapy was greater than that calculated for the sum of the individual drug effects in limiting the development of herpetic skin lesions in mice. In several experiments, combination therapy totally eliminated all signs of infection. This synergistic chemotherapeutic efficacy was evident in infections caused by ACV-susceptible as well as several ACV-resistant HSV-1 strains. These results indicate that this combination therapy may provide a significant improvement in clinical responses over single-agent topical therapy.